STRATEGI PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH NEGERI (MAN) 1 MEDAN - Rawi Nasution, Muhammad Fadlan; Bagus Sanjaya, Mario; Abdurrahman, Abdurrahman (Yayasan Haiah Nusratul Islam, 2023)
To achieve successful learning, the role of the teacher is very necessary as the key to successful education. The learning strategies brought by the teacher greatly influence the achievement of the learning stage. This research was conducted with the aim of looking at Arabic language learning strategies and seeing how effective they are for students. The research method used in this research is a qualitative method that uses data collection techniques through interviews and observation. The results of this research are that the strategy used by teachers in learning Arabic at MAN 1 Medan is an expository strategy where the teacher focuses on delivering material in the first semester to groups of students as their introduction to the material. Meanwhile, the learning method applied is in the form of reading and writing Arabic.